PAINTING-COLOR ART: HISTORICAL, AESTHETIC AND CONTEMPORARY ANALYSIS - Samadova Farzona Soxibovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: this article analyzes the art of painting - the culture of image expression through colors, its historical roots, stages of formation and modern trends.Colorartis considered not only as a means of aesthetic expression, but also as an important type of art that illuminates human thinking, the spiritual world and social consciousness.